Traffic induced variability in dynamic properties of cable stayed bridge. - Zhang, Q.W (Earthquake engineering & structural dynamics.)
The traffic induced variability in the dynamic properties of a cable stayed bridge is investigated using ambient vibration measurements. Under a relatively steady wind and temperature environment, the ambient vibration test was conducted on the bridge with normal traffic conditions and totally 24 h acceleration response time histories were recorded. These data are divided into 12 sections with each data section containing 2 h measurements. Thereby the modal variability due to changing traffic loading is investigated through post-processing of the data in each section in both amplitude and frequency domains. The result indicates that the natural frequencies of the global modes can exhibit as much as 1 percent variation within a day. The modal amplitudes of each mode as well as the modal deflection at each measurement position vary insignificantly. The damping ratios however are sensitive to the vibration intensity, especially when the deck vibration exceeds a certain level.